1991
DOI: 10.1016/0014-5793(91)80541-a
|View full text |Cite
|
Sign up to set email alerts
|

Absence of insulinotropic glucagon‐like peptide‐I(7–37) receptors on isolated rat liver hepatocytes

Abstract: The effect~ of lglucagon and the llluc, tlon-like I'.cptide GLP-1(7=37) were compared in rat liver hepatocytes. Gluea¢8on elevated cAMP, elevated intracell ular free calcium {ICon*J0, activated phosphoryht~ and stin)t=lated illu¢oneogenesi~, wherea~ GLP.I(?~37) was without effect on any of the~¢ parameters, GLP-1:(7=37] did not block any of the actions of glaeagon, The lllucaBon analog, de( Hi,= t IGItP] glucagon an'tide, was a partial agonist in liver, but al~o was an effective antagonist of Illucagon actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 26 publications
5
15
0
Order By: Relevance
“…There are numerous reports of the presence of GLP-1 receptors in liver (2,42), and in in vitro studies GLP-1 per se has been shown to increase glycogen synthesis in liver (2). However, the presence of such hepatic receptors remains controversial (2,4,6,42). The utilization of a GLP-1 receptor antagonist such as exendin-(9 -39) could be useful in future studies to clarify this mechanistic and important physiological issue.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous reports of the presence of GLP-1 receptors in liver (2,42), and in in vitro studies GLP-1 per se has been shown to increase glycogen synthesis in liver (2). However, the presence of such hepatic receptors remains controversial (2,4,6,42). The utilization of a GLP-1 receptor antagonist such as exendin-(9 -39) could be useful in future studies to clarify this mechanistic and important physiological issue.…”
Section: Resultsmentioning
confidence: 99%
“…Most (4,5,41), but not all (48), investigators have been unable to find evidence of GLP-1 receptor gene expression in hepatic cells. Although most of these analyses have been performed in rat tissues (4,5,41,48), two groups have been unable to find GLP-1 receptor mRNA in extracts from human liver (14,46). Several investigators have demonstrated GLP-1 receptor expression in kidney extracts (5,48), so it is possible that GLP-1 selectively inhibits renal glucose production.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of intraportal GLP-1 on impulse traffic in vagal afferent sensory nerve fibers were also resistant to exendin 9 -39 (219). The liver has repeatedly been reported to be a target for GLP-1, although initial careful studies indicated that hepatocytes did not express GLP-1 receptor (17). Thus GLP-1 has been reported to bind to rat hepatic membranes but without influencing adenylate cyclase activity, as expected from the classical GLP-1 receptor (308).…”
Section: Whole Body Effects Peripheral Effects and Effects On Inmentioning
confidence: 96%